Better PROMs and higher return-to-sport rate after modular bicompartmental knee arthroplasty than after total knee arthroplasty for medial and patellofemoral compartment osteoarthritis - Deng, Wang; Shao, Hongyi; Tang, Hao; Tang, Qiheng; Wang, Zhaolun; Yang, Dejin; Zhou, Yixin (Frontiers in Surgery, 2023)
Background: Theoretical advantages of bicompartmental knee arthroplasty (BKA) over total knee arthroplasty (TKA) for bicompartmental (medial combined with patellofemoral) osteoarthritis (OA) are still unclear. This study aimed to compare patient-reported outcome measures (PROMs) and return-to-sport (RTS) rate between modular BKA and TKA in early follow-up. Methods: Twenty-five consecutive modular BKA cases with a minimum 2-year follow-up were matched with 50 TKA cases at 1:2 ratio. Demographic data and preoperative functional scores, including the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Knee Society Scores (KSSs), were analyzed to ensure comparability. Postoperative WOMAC score, KSS, range of motion (ROM), Forgotten Joint Score-12 (FJS-12), and RTS rates were compared. Operative time and blood loss were also analyzed. Results: Significant differences in the WOMAC-function (median 97.1 vs. 89.7, p<0.001) and KSS-function (median 90.0 vs. 80.0, p=0.003) scores were identified between the BKA and TKA groups. ROM was significantly greater in the BKA group than in the TKA group (median 125.0° vs. 120.0°, p=0.004), in addition to the FJS-12 (median 89.6 vs. 53.1, p<0.001). The overall RTS rate was significantly higher in the BKA group than in the TKA group (71.6% vs. 56.5%, p=0.039). Operative time was significantly longer in the BKA group than in the TKA group (median 105.0 min vs. 67.5 min, p<0.001), but blood loss was similar (median 557.6 mL vs. 450.7 mL, p=0.334). Conclusions: Modular BKA demonstrated better functional recovery, better joint perception, and higher RTS rate than TKA; thus, modular BKA can be a good alternative for bicompartmental OA.